CORRUPTION IN PENAL INSTITUTIONS: DARK SOCIAL REINTEGRATION, NATIONAL DEFENSE IS THREATENED - Adrianus Meliala (Polteknik Ilmu Pemasyarakatan, 2021)
One, among many, profound problems found relating prison and remand management in Indonesia is corruption. Not only among warden and inmates but corruption may prevail among inmates. Sometimes, rather sophisticated modes of action found whereas inmates control corruption taken by outside people. This article argues 6 (six) socio-criminological theories which may explain this phenomenon. Such failure regarding why corruption occurs, as uniquely explained by each theories, may result the prolong prison corruption which endangers national resilience.